Response to olaparib in metastatic castration-resistant prostate cancer with germline BRCA2 mutation: a case report - Yi Ma; Lijie He; Qianwen Huang; Shuang Zheng; Zhiqiang Zhang; Hongshi Li; Shuang Liu (BMC, 2018)
Abstract Background Prostate cancer is a heterogeneous disease, meaning patients would benefit from different treatment strategies based on their molecular stratification. In recent years, several genomic studies have identified prostate cancers with defects in DNA repair genes. It is known that the PARP inhibitor, olaparib, has a significant synthetic lethal effect on tumors with BRCA 1/2 mutations, particularly in ovarian and breast cancer. Case presentation In this study, we describe a patient with metastatic castration-resistant prostate cancer (mCRPC) containing a BRCA2 germline mutation who underwent olaparib treatment. The efficacy of the treatment was monitored by serum TPSA level as well as mutation levels of circulating tumor DNA (ctDNA) using next-generation sequencing (NGS). The patient responded to the olaparib treatment as indicated by the minimal residual levels of TPSA and tumor-specific mutations of ctDNA in plasma after four months of treatment, although the patient eventually progressed at six-month post-treatment with significantly elevated and newly acquired somatic mutations in ctDNA. Conclusions Our study provides evidence that mCRPC with BRCA2 germline mutations could response to PARP inhibitor, which improves patient's outcome. We further demonstrated that NGS-based genetic testing on liquid biopsy can be used to dynamically monitor the efficacy of treatment.